Clinical Characteristics and Immune Responses in Children with Primary Ciliary Dyskinesia during Pneumonia Episodes: A Case-Control Study - Danli Lu; Wenhao Yang; Rui Zhang; Yan Li; Tianyu Cheng; Yue Liao; Lina Chen; Hanmin Liu (MDPI AG, 2023)
Objective: This study explored the clinical features and immune responses of children with primary ciliary dyskinesia (PCD) during pneumonia episodes. Methods: The 61 children with PCD who were admitted to hospital because of pneumonia were retrospectively enrolled into this study between April 2017 and August 2022. A total of 61 children with pneumonia but without chronic diseases were enrolled as the control group. The clinical characteristics, levels of inflammatory indicators, pathogens, and imaging features of the lungs were compared between the two groups. Results: The PCD group had higher levels of lymphocytes (42.80% versus 36.00%, p = 0.029) and eosinophils (2.40% versus 1.25%, p = 0.020), but lower neutrophil counts (3.99 versus 5.75 × 109/L, p = 0.011), percentages of neutrophils (46.39% versus 54.24%, p = 0.014), CRP (0.40 versus 4.20 mg/L, p < 0.001) and fibrinogen (257.50 versus 338.00 mg/dL, p = 0.010) levels. Children with PCD and children without chronic diseases were both most commonly infected with Mycoplasma pneumoniae (24.6% versus 51.9%). Children with PCD had significantly more common imaging features, including mucous plugging (p = 0.042), emphysema (p = 0.007), bronchiectasis (p < 0.001), mosaic attenuation (p = 0.012), interstitial inflammation (p = 0.015), and sinusitis (p < 0.001). Conclusion: PCD is linked to immune system impairment, which significantly contributes to our understanding of the pathophysiology of this entity.